Resection and primary anastomosis in necrotizing enterocolitis. - Ade-Ajayi, N (1996)
Necrotizing enterocolitis (NEC) is the most common surgical emergency in the newborn. Up to half of babies with NEC develop advanced disease requiring surgical intervention. Options include peritoneal drainage under local anaesthetic, enterostomy only, resection and enterostomies, and resection with primary anastomosis. Resection with enterostomies is favoured by many paediatric surgeons but management of neonatal enterostomies can be difficult. The outcome of 26 infants undergoing surgery for advanced NEC over a 2-year period is reviewed. Resection and primary anastomosis was possible in 18 infants of whom two (11%) died. Recurrent NEC developed in four (22%) and strictures in three (17%) of these infants. An initial enterostomy was fashioned in eight infants, three following resection of necrotic intestine and five as a proximal diverting stoma in infants with pan-intestinal involvement. Five of these eight infants died (63%), giving an overall mortality of 27%. Primary anastomosis is an effective procedure following resection of grossly involved intestine in infants with NEC. The mortality and morbidity in this series compared well with those reported for staged procedures.